CONTINUITY AND DISCONTINUITY OF GENDER-NATURE RELATIONS IN DH LAWRENCE'S 'THE WOMAN WHO RODE AWAY' - Winarti Winarti; Anindhiasti Ayu Kusuma Sari; Ginarsiwi Mayangseto; Fitria Naimatul Istiqomah (Leksema: Jurnal Bahasa dan Sastra, 2022)
Oppressions of nature and gender are two things that are interrelated. Both require a struggle that leads to the liberation of nature and women called ecofeminism. The Gender-nature relations can be found in literary works as reflections of the reality that surrounds the author. Through literary works, issues related to gender and nature are raised by the author as a form of ecofeminist struggle, that all forms of damage done by humans to nature will have an impact on the preservation of nature in the future. The objective of this study was to find out the continuity and discontinuity between nature and gender as part of the ecofeminism discourse in the short story The Woman Who Rode Away written by DH Lawrence. The method used to collect data was observation through close reading to both the story, as the primary data source, and other texts from journals and reference books as the secondary data sources. The result shows that the narratives of ecofeminism are evident in the fiction. The story tells the position of men as the masters in nature who have the power over all things. The depiction of male characters as the figures who tend to oppress women becomes a part of discontinuity toward nature in the story. This is different from the depiction of the female character who is considered as a caretaker of nature and is able to build a continuity of harmonious relationship between human and nature. In conclusion, the story reflects unbalanced relationships between gender and nature.